Pengaruh Talent Management, Employee Engagement dan Kepuasan Kerja terhadap Komitmen Organisasi pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia di Walikota Tangerang Selatan - Novia Rachmadhani; Maswanto Maswanto (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the influence of talent management, employee engagement, and job satisfaction on organizational commitment at the Civil Service and Human Resource Development Agency of South Tangerang City. The method used is a quantitative approach with an associative and comparative research design. Data were collected through questionnaires distributed to 50 employees, and the analysis was carried out using multiple linear regression. The results showed that all independent variables had a positive and significant influence on organizational commitment. Specifically, talent management showed a regression coefficient of 0.538, employee engagement 0.529, and job satisfaction 0.687. The R² value of 0.942 indicates that 94.2% of the variation in organizational commitment can be explained by these three variables. This finding indicates the importance of good HR management to improve employee commitment in public organizations.